MIKROBAENDOFITIK DARI TAMAN NASIONALBATANG GADIS SUMATERA UTARA: POTENSINYA DALAM MENGHASILKAN SENYAWA ANTIMIKROBATERHADAPMIKROBAPATOGEN - Sukiman, Harmastini; Lekatompessy, Sylvia; Widowati, Tiwit (BERITA BIOLOGI, 2009)
Batang Gadis National Park (TNBG) is one of the tropical forests in North Sumatra with megabiodiversity of flora and fauna including microorganism. Endophytic microbes conservation from varieties of forest plants in Batang Gadis National Park has been completed. Nineteen endophytes isolates from TNBG have been screened for their potential on producing bioactive compound against the pathogenic bacteria. Qualitative screening has been done using the growth agar media and identified the clear zone appeared surrounding the bacteria colony. The result indicated that isolate MSCI 87.4 showed high strengthening secresion (4.35) againts Xanthomonas campestris, whereas isolate MSCI 37.1 showed high secretion against Bacillus subtilis (2.69) and Escherichia coli (2.60). Isolate MSCI 37.4 showed potential on producing bioactive compound againts Staphylococcus aureus (4.41). Isolates MSCI 87.4, MSCI37.1, MSCI 37.4 and MSCI 58.1 even could produce bioactive compound against four pathogenic bacteria that are Xanthomonas campestris, Bacilus subtilis, Escherichia coli and Staphylococcus aureus, whereas isolate MSCI 15.5b potential on producing bioactive compound against two isolates namely Xanthomonas campestris and Bacillus subtilis. The endophytes bacteria mainly belong to the Gram negative group and four out of nineteen isolates tested belong to the Gram positive group. The cell mainly coccus and only one is bacilli without fiagella. The five most potential isolates has been maintained under freeze dried condition for futher conservation and study. Thin Layer Analysis using semipolar organic separation solution showed that most isolates identified were able to produce bioactive compound except two isolates i.e. MSCI 48.4a and MSCI 53.1; however further analysis is needed to confirm the product.